KOROSI BAJA KARBON API 5L GRADE B SEBAGAI FLOWLINE PRODUKSI GAS ALAM - Setiawan, Adhi; Fajrin, Alfinura; Munir, M. Miftahul; Ari, M. (Universitas Nahdlatul Ulama Sidoarjo, 2018)
Corrosion that occurs in a gas flowline is a serious problem because it can cause leaks that lead to material loss and environmental pollution. The aims of this research were to analyze the corrosion occurred in gas flowline of carbon steel 5l Grade B and the effect of inhibitor TIC-8002 GCI to the corrosion rate of metal. This research was conducted using SEM-EDX to analyze and produce various types of metals and corrosion crust. Metals corrosion test and the effect of inhibitors on the corrosion rate of metals were carried out by linear polarization methods. The result of SEM-EDX showed that inner pipe surface occurred pitting corrosion caused by dissolved chloride ions in the electrolite that flows in the pipeline. The result of XRD showed that corrosion products of carbon steel were Fe2O3 and FeOOH. The result of linear polarization showed that the corrosion rate of steel about 0.642 mmy without using inhibitor. The addition of an inhibitor can reduce the corrosion rate in carbon steel. The increase in inhibitor concentration from 10 ppm to 50 ppm can reduce the corrosion rate from 0.633 mmy to 0.394 mmy along with an increase in inhibition efficiency from 1.32% to 38.6%.